Peran Guru Teknologi Informasi dan Komunikasi (TIK) dalam Pembelajaran Mandiri Siswa di SMP Negeri 02 Bengkulu Tengah - Suhirman Suhirman; Friti Sulastri; Hafidzah Nurhasanah; Ai Siti Hodijah (Al-Khair Journal: Management Education, 2024)
Abstract: The use of technology in the process of independent learning is still relatively low, marked by social networks, e-mail or skype, sufing the internet only as communication in cyberspace. This study aims to describe the role of ICT teachers in independent learning in SMP Negeri 2 Bengkulu Tengah. Using a descriptive qualitative method. The results of the study show that the role of ICT teachers in independent learning is very important such as teachers as learning designers, facilitators, managers, demonstrators, supervisors, motivators, and as elevators. ICT teachers think positively and always want to progress in learning ICT, have a high awareness to make changes, read journals, learn independently by exploring to find potential and talents, and participate in training, comparative studies to develop abilities, skills to continue to develop in educating students to learn independently. Independent learning can utilize ICT such as E-Learning, powerpoint, e-mail, youtube, learning videos, websites and various learning applications that can be used independently by teachers and students in gaining knowledge, knowledge and information about learning independently. So it can be concluded that ICT teachers can play a role in improving students' independent learning. Thus, it can be suggested that to increase student independent learning, increase the role of ICT teachers in schools.Keywords: The Role of Information and Communication Technology Teachers, Student Independent Learning. Abstrak: Penggunaan teknologi dalam proses pembelajaran mandiri masih tergolong rendah, ditandai jejaring sosial, e-mail atau skype, sufing internet hanya sebagai komunikasi di dunia maya. Penelitian ini bertujuan untuk mendeskripsikan peran guru TIK dalam pembelajaran mandiri di SMP Negeri 2 Bengkulu Tengah. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa peran guru TIK dalam pembelajaran mandiri menjadi sangat penting seperti guru sebagai perancang pembelajaran, fasilitator, pengelola, demonstrator, pembimbing, motivator, dan sebagai elevator. Guru TIK berfikir positif dan selalu ingin maju dalam mempelajari TIK, memiliki kesadaran yang tinggi untuk melakukan perubahan, membaca jurnal, belajar mandiri dengan bereksplorasi menemukan potensi dan bakat, ikut pelatihan, studi banding untuk mengembangkan kemampuan, keterampilan untuk terus berkembang dalam mencerdaskan siswa belajar secara mandiri. Pembelajaran mandiri dapat memanfaatkan TIK seperti E-Learning, powerpoint, e-mail, youtube, video pembelajaran, situs dan berbagai aplikasi pembelajaran yang dapat digunakan secara mandiri oleh guru dan siswa dalam mendapat ilmu, pengetahuan dan informasi mengenai pembelajaran secara mandiri. Sehingga dapat disimpulkan bahwa guru TIK dapat berperan dalam meningkatkan pembelajaran mandiri siswa. Dengan demikian, dapat disarankan, untuk meningkatkan pembelajaran mandiri siswa, maka tingkatkan peran guru TIK di sekolah.Keywords: Peran Guru Teknologi Informasi dan Komunikasi, Pembelajaran Mandiri Siswa.